First‐Principles Study on the Crystalline Ga4Sb6Te3 Phase Change Compound. Issue 3 (22nd September 2020) - Baratella, Dario; Dragoni, Daniele; Ceresoli, Davide; Bernasconi, Marco
Abstract : The Ga 4 Sb 6 Te 3 compound on the GaSb – Sb 2 Te 3 pseudobinary tie‐line is proposed in the literature as a phase change material with high crystallization temperature. Herein, the crystal structure of this compound is uncovered by means of a genetic algorithm and electronic structure calculations based on density functional theory. As opposed to the parent GaSb compound which crystallizes in the zincblende structure, the Ga 4 Sb 6 Te 3 compound features an octahedral‐like coordination for Ga as well as for Sb and Te atoms. Other structures close in energy to the ground state are also proposed, including some with a tetrahedral‐like coordination of Ga atoms. Raman spectra computed within density functional perturbation theory and an empirical Bond Polarizability Model are shown to be able to discriminate among the different possible local environments of Ga atoms. Abstract : Possible structures for the crystalline Ga 4 Sb 6 Te 3 phase change compound are proposed on the basis of a genetic algorithm and density functional total energy calculations. Competitive structures with either octahedral or tetrahedral coordination for Ga atoms are found. Phonon calculations show that the different structures can be discriminated by Raman spectroscopy.